Evidence-based decision-making in speech-language pathology via video-based telepractice—A qualitative video interaction analysis - Barthel, Maria; Wittmar, Silke; Borgetto, Bernhard; Leinweber, Juliane (Frontiers in Communication, 2023)
Introduction: In speech-language pathology, there is a constant need to make evidence-based decisions based on the patient's needs and goals, speech-language pathologist's clinical expertise, and external evidence. During the COVID-19 pandemic, it was possible for the first time in Germany to implement video-based telepractice in the outpatient care of speech-language pathology. This study aimed to find out how evidence-based decisions are made in video-based telepractice and what forms of evidence are used.Methods: Speech-language pathologists who were working in outpatient services recorded their video-based telepractices for the research project. Five recorded video-based telepractices were transcribed using a simple transcription system and video interaction analysis was used to analyze the video recordings based on grounded theory methodology.Results: Interactions between patients and speech-language pathologists are characterized by evidence-based decisions that can be observed. Speech-language pathologists make decisions based on their clinical expertise, patient-related experiences, and patient self-assessments. There is little evidence of negotiation between patients and speech-language pathologists to make joint decisions.Results showed that speech-language pathologists do not explicitly name external evidence to justify their decisions to patients. Shared decision-making is encouraged by a participative interaction between patients and speech-language pathologists. However, there was a predominant paternalistic interaction in which the speech-language pathologists made decisions on their own. To represent the decision-based interactions between patients and speech-language pathologists in a video-based therapy session, a process model was developed. Discussion: Evidence-based and shared decision-making are important in speech-language pathology to provide patient-centered treatments. The exchange of information between the patient and the speech-language pathologist is important in order to make joint decisions based on these different levels of knowledge. In this way, the patient becomes an active participant in the digital treatment, in the video-based telepractice. As a result, the quality of care can be improved. Further research should reconstruct the implicit (possible) use of external evidence.